A Review Study on Medicinal Properties of Psidium Guajava (International Journal of Innovative Research in Computer Science & Technology, 2021)
Guava is a plant local to Tropical America  and one of the most well-known in the Myrtaceae family. In  contrast with different organic products, guava is untreated  with synthetic compounds, making it a better choice. It has  for quite some time been utilized as a homeopathic spice to  treat an assortment of illnesses all over the planet. Oleanolic  corrosive, tannins, quercetin, triterpenes, ursolic corrosive, a  pentacyclic triterpenoid, saponins, carotenoids, amritoside, lectins, guajanoic corrosive, leucocyanidin, beta-sitosterol,  and avail are among the dynamic fixings. Guava has  antibacterial, hostile to malarial, against diarrheal, calming,  against malignant growth, against hyperglycemic, and cell  reinforcement properties, among others. A few examinations  have uncovered that guava contains various pharmacological  dynamic parts that are liable for an assortment of  biochemical exercises, including antidiabetic, antimicrobial,  antidiarrheal, against oxidant, hostile to pyretic, cardioactive,  hepatoprotective, immunomodulatory, spasmolytic, and  contractile impacts, which are talked about further in the  survey. This paper was assembled to bring issues to light  with regards to pharmacological exercises and how they can  be utilized to treat an assortment of problems and infections.  Guava has a wide scope of healthful and therapeutic properties. Contingent upon the species, the natural products  are 4-12 cm long and have a round or oval shape (red,  strawberry, and grayish). The tree, which has a place with the  Myrtaceae family, is essentially filled in tropical and  subtropical environments. Whenever analyzed, the pink  assortment of guava has the most elevated restorative worth.  Antidiarrheal, antihypertensive, antilipidemic, anticancer,  and other medical advantages can be found in both foods  grown from the ground leaves.
Keywords: Fruits; Guava; Herb; Medicinal; Psidium guajava; Tree